REPRESENTASI BUDAYA BETAWI DALAM BUKU SAHABATKU INDONESIA: BAHAN AJAR BIPA UNTUK UMUM - Nova, Indah Fauziah (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This study discussed the elements of Betawi culture contained in teaching materials of Indonesian language teaching for Foreign Speakers (BIPA) for the public. The paper aimed to describe and understand the representation of Betawi culture as documented in the BIPA textbook published by The Agency for Language Development and Cultivation, Ministry of Education, Culture, Research, and Technology. The teaching material entitled My Indonesian Friend (Reading Jakarta: Traditional Culture BIPA 3) is used as a diplomatic tool in a subtle form to introduce Indonesian culture. Apart from that, the book was also used as a reference teaching material that supports BIPA learning by teachers and institutions administering the BIPA program. The method used in this paper was a qualitative descriptive method. The technique used in this study was reading and note-taking technique. The object of this research was the book entitled My Friends of Indonesia (Reading Jakarta: Traditional Culture BIPA 3) which was published in 2019. The cultural elements in this research were elaborated and classified by referring to the universal cultural elements of Koentjaraningrat (1981). In this study, there are six types of Betawi culture found, such as religious systems and ceremonies, social systems and organizations, knowledge systems, arts, livelihood systems, and technology and equipment systems.